Total thyroidectomy in Basedow-Graves’ disease treatment: our experience - BARBUSCIA, M. (G Chir, 2015)
In the present study the authors, after a short historical description of the Basedow-Graves’ disease, describe their case-study gathered over the last five years. They mention the most widely accepted hypothesis regarding disease’s etiology, strongly linked to autoimmune disorders, and the role that some viral agents (Coksackie B and HTLV-II) may have in initiating autoantibody production and T cells activation in genetically predisposed individuals. Basic and clinical aspects of the diagnosis and disease treatment, highlighting the use of thyroidectomy, are addressed. They conclude that total thyroidectomy represents today the treatment of choice, which, after appropriate preparation to reach the euthyroidism condition, can ensure a successful cure.